Diversity‐dependent plant–soil feedbacks underlie long‐term plant diversity effects on primary productivity. Issue 4 (8th April 2019) - Guerrero‐Ramírez, Nathaly R.; Reich, Peter B.; Wagg, Cameron; Ciobanu, Marcel; Eisenhauer, Nico
Abstract: Although diversity‐dependent plant–soil feedbacks (PSFs) may contribute significantly to plant diversity effects on ecosystem functioning, the influences of underlying abiotic and biotic mechanistic pathways have been little explored to date. Here, we assessed such pathways with a PSF experiment using soil conditioned for ≥12 yr from two grassland biodiversity experiments. Model plant communities differing in plant species and functional group richness (current plant diversity treatment) were grown in soils conditioned by plant communities with either low‐ or high‐diversity (soil history treatment). Our results indicate that plant diversity can modify plant productivity through both diversity‐mediated plant–plant and plant–soil interactions, with the main driver (current plant diversity or soil history) differing with experimental context. Structural equation modeling suggests that the underlying mechanisms of PSFs were explained to a significant extent by both abiotic and biotic pathways (specifically, soil nitrogen availability and soil nematode richness). Thus, effects of plant diversity loss on plant productivity may persist or even increase over time because of biotic and abiotic soil legacy effects.